Monitoring of VOCs during In vitro pathogenesis of Rigidoporus microporus and Fulvifomes siamensis using SPME GC-MS and electronic nose - Izzah Hazirah Bte Junin (Nanyang Technological University, 2023)
E-Nose can be a tool for early diagnosis of wood rot fungi by detecting volatile organic compounds (VOCs) released by diseased trees. It is more affordable and less invasive than traditional Immunology-based and PCR-based assays. This thesis tested E-Nose discrimination ability of inoculated wood blocks of four common urban tree species (Khaya, Rain Tree, Casuarina, and Angsana) with pathogenic fungi, Fulvifomes siamensis, and Rigidoporus microporus, at 2, 4, 6 and 8 weeks post-inoculation. E-Nose can discriminate inoculated wood blocks from the non-inoculated from 2 weeks onwards. Results from SPME GC-MS identified signature VOCs present in F. siamensis-inoculated wood blocks - Benzene, 1,2,4,5-tetrachloro-3,6-dimethoxy- and Benzene, 1,4-dichloro-2,5-dimethoxy-. However, R. microporus-inoculated wood blocks lacked any signature volatile. E-Nose could differentiate wood blocks of different tree species, except for 8 weeks post-inoculation by F. siamensis, likely due to dominance by fungus signature volatiles. E-Nose's distinctive clustering on different air samples, with nitrogen as baseline gas, proves variability in air VOCs and further supports using nitrogen for consistent baseline and better sensor responses. Multiple models also tested E-Nose identification capability. Future studies should follow the progression of in vivo pathogenesis and confirm the utility of E-Nose for real-life application of early-stage infection by pathogenic fungi.